2022
DOI: 10.1155/2022/8613384
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis on the Effects of Electric Acupuncture on Neural Functional Recovery and Related Pathways of Rats after Spinal Cord Injury

Abstract: Background. Spinal cord injury (SCI) is a type of damage to the central nervous system (CNS) caused by various factors. The secondary injury of SCI is more complicated. Studies have found that electroacupuncture can help the recovery of nerve function during spinal cord injury. Therefore, this study explored the efficacy of electroacupuncture on complications after spinal cord injury through meta-analysis. Methods. Relevant literatures published from January 2010 to March 2022 were searched with “Electric acup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The affected individual’s resulting inability to work (labor) and the costs of long-term treatment impose a heavy financial burden on their family and the wider community [ 1 ]. Despite concerted efforts focused on SCIs in global terms, no effective breakthrough has yet been made toward a cure for the neurological dysfunction caused by an SCI [ 2 , 3 ]. Thus, it is imperative to further explore the pathophysiological mechanism of and to develop effective rehabilitation strategies for SCIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The affected individual’s resulting inability to work (labor) and the costs of long-term treatment impose a heavy financial burden on their family and the wider community [ 1 ]. Despite concerted efforts focused on SCIs in global terms, no effective breakthrough has yet been made toward a cure for the neurological dysfunction caused by an SCI [ 2 , 3 ]. Thus, it is imperative to further explore the pathophysiological mechanism of and to develop effective rehabilitation strategies for SCIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proved that EA can not only relieve neuropathological pain after SCI, 26 promote the repair of motor function of injury, 27 but also improve intestinal peristalsis 28 and bladder dysfunction 29 caused by injury. It plays a particular role in the process of neuronal repair post‐SCI 30–32 . However, the mechanism of EA therapy to improve the repair of nerve function after SCI is complex and diverse, which still needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a particular role in the process of neuronal repair post‐SCI. 30 , 31 , 32 However, the mechanism of EA therapy to improve the repair of nerve function after SCI is complex and diverse, which still needs further study. This study first clarified the regulatory effect of PNN on inhibitory interneurons in SCI tissues by RNA‐seq analysis and suggested that NCAN may be an important factor for the action of PNN through a protein–protein interaction network.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%